PENGARUH KUALITAS PRODUK, PERSEPSI HARGA,PROMOSI DAN LOKASI TERHADAPKEPUTUSAN PEMBELIAN (Studi Pada Rumah Makan Ayam Geprek di Kota Semarang) - Nunung Pamungkas, 12.05.51.0048 (Students Journal of Economic and Management, 2017)
Purchase consumer behavior is unique with preference everyone to a the products of different - different.It affected by many factors among them quality products, perception prices, promotion, locations and other - other.The purpose of this study is to find and analyze the influence of quality products, perception prices, promotion and location of the decision to buy chicken geprek in semarang city Population this research is consumers who buy chicken geprek idol within the city of semarang .Sample in this research as many as 100 people .Technique the sample collection use proposive sampling .As for criteria sample in this research was consumers from restaurants chicken geprek idol already over once buy at home eating chicken geprek idol .Instrument the analysis used is the validity , reliability and linear regression multiple . The results of the analysis can be concluded that: quality products have had a positive impact of the decision the purchase .Perception the price is not influential of the decision the purchase .Promotion do not affect of the decision the purchase .Location have had a positive impact of the decision the purchase. Password: quality roducts , perception price , promotion , location and intention buy